A critique of shareholder primacy under UK takeover law and the continued imposition of the Board Neutrality Rule. Issue 4 (13th July 2015) - Nyombi, Chrispas
Abstract : Purpose: – The purpose of this paper is to determine whether the Board Neutrality Rule and the primacy afforded to shareholders during takeovers is justified under common law and policy. Design/methodology/approach: – The paper provides a detailed assessment of the role play by the board neutrality rule and whether this is supported by takeover law and Company law. A review of case law and statutes is provided. The paper is largely analytical. Findings: – The paper finds little justification for the continued imposition of the Board Neutrality Rule. Originality/value: – The paper adds to the growing body of research literature which has analysed the role played by the Board Neutrality Rule during takeovers.